Percutaneous Transluminal Balloon Valvuloplasty in Congenital Pulmonary Valve Stenosis - Rey, Christian (1986)
From March 1984 to September 1986, 49 transluminal balloon valvuloplasties (TBVs) were performed in 44 consecutive patients with congenital pulmonary valve stenosis, aged 1 day to 60 years. Seventeen of the patients were infants aged less than 1 year, five of whom were neonates. The peak systolic gradient was greater than 50 mm Hg (mean, 80.0 mm Hg) in 36 patients and was less than 50 mm Hg (mean, 35.4 mm Hg) in eight. A single balloon catheter was used in 41 cases, and two balloon catheters were used in eight cases. In patients with a gradient greater than 50 mm Hg, the mean right ventricular peak systolic pressure was reduced from 99.8 to 51.8 mm Hg, and the mean transvalvular gradient was reduced from 80.0 to 22.4 mm Hg. In infants and neonates, the mean right ventricular pressure expressed as a percentage of systemic pressure decreased from 122.2% to 63.5%. Follow-up cardiac catheterization 1 to 17 months later (in 19 cases) revealed no significant change in the right ventricular systolic pressure (which had decreased from 53.0 to 48.5 mm Hg) or the peak systolic pressure gradient (which had decreased from 29.0 to 24.5 mm Hg), in comparison with the changes seen immediately after TBV. Thus, TBV is an effective method of relieving pulmonary stenosis in patients of all ages, including neonates. (Texas Heart Institute Journal 1986; 13:387-392)